Analisis Miskonsepsi Calon Guru Sekolah Dasar pada Matakuliah Konsep Dasar Matematika dengan Menggunakan Three-Tier Diagnostic Test Dilengkapi Certainty Of Response Index. - Nurwahida Nurwahida; Nilam Permatasari Munir (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
This research is a quantitative descriptive study that aims to analyze the misconceptions of students of the PGMI Study Program in the subject of Basic Mathematics Concepts, especially the concept of integers and fractions. The subjects of this study were all students of the PGMI IAIN Palopo Study Program in semester 1. The research sample was 33 students using purposive sampling technique. Data collection uses test and non-test techniques. The test uses a three-tier diagnostic test instrument equipped with CRI (Certainty of Response Index) to identify misconceptions. Non-test uses interviews with students to find out the reasons why students experience misconceptions. The data analysis technique used descriptive percentage analysis. The results of the analysis show that the percentage of students who experience misconceptions about the concept of integers and fractions, 24.2%, including the criteria for Understanding Concepts Well (PKDB), 6.1%. including the criteria for understanding the concept but not sure (PKTTY), 25.8% including the criteria for not understanding the concept (TPK), and the remaining 43.9% experiencing misconceptions. The highest percentage of misconceptions is found in questions about fractions in story problems 57.6%. The lowest percentage of misconceptions is found in questions about the operation of adding mixed fractions at 30.3%. The main factors that cause misconceptions are sourced from learning sources and their own thoughts.